1982
DOI: 10.1097/00000658-198205000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Is Carcinoma of the Gallbladder a Curable Lesion?

Abstract: Carcinoma of the gallbladder is an uncommon, but not rare tumor that is associated with a 5% five-year survival rate after resection and this rate has not appreciably improved over the last decades in most series. Nevin et al.(20) however have reported that favorably staged gallbladder cancers (according to histologic grade and depth of invasion) have a relatively good prognosis. They quoted an overall five-year survival of 21% in 66 patients. Most of the surviving patients (11) were in the favorably staged ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(49 citation statements)
references
References 21 publications
1
47
0
Order By: Relevance
“…N a k a m u r a et al 1 1 a n d Miyazaki et al 1 2 h a v e achieved better survival rates from extensive hepatectomy in cases with direct hepatic invasion than in previously reported cases, in which hepatic wedge resection had been performed. 8 ' 9 According to our study findings, in which the distance between the margin of direct hepatic invasion and hepatic metastasis had no correlation with the extent of direct hepatic invasion, occult localized hepatic metastasis around the gallbladder bed may not be removed by hepatic wedge resection for advanced gallbladder cancer. In view of this possibility, substantial hepatectomy, such as resection of S4a and S5, resection of S4a, S5, and S6, or extended right hepatectomy might be a better choice in cases with direct hepatic invasion but not necessarily in cases with involvement of the hepatoduodenal ligament.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…N a k a m u r a et al 1 1 a n d Miyazaki et al 1 2 h a v e achieved better survival rates from extensive hepatectomy in cases with direct hepatic invasion than in previously reported cases, in which hepatic wedge resection had been performed. 8 ' 9 According to our study findings, in which the distance between the margin of direct hepatic invasion and hepatic metastasis had no correlation with the extent of direct hepatic invasion, occult localized hepatic metastasis around the gallbladder bed may not be removed by hepatic wedge resection for advanced gallbladder cancer. In view of this possibility, substantial hepatectomy, such as resection of S4a and S5, resection of S4a, S5, and S6, or extended right hepatectomy might be a better choice in cases with direct hepatic invasion but not necessarily in cases with involvement of the hepatoduodenal ligament.…”
Section: Discussionmentioning
confidence: 73%
“…One reason for the poor outcome might be excessively limited hepatic resection; wedge resection of the gallbladder bed is the most popular procedure. 8,9 Some surgeons have reported that more extensive hepatectomy such as extended right hepatic lobectomy offers a better prognosis. 10_12 We propose, in agreement with the findings of other investigations about hepatic metastasis from colorectal cancer, 13 ' 14 that hepatic recurrence after resection for advanced gallbladder carcinoma is due, at least in part, 11 metastatic lesions were located within the portal tracts or accompanied by invasion into the portal tracts.…”
mentioning
confidence: 99%
“…The most logical surgical approach to carcinoma of the gallbladder, therefore, is cholecystectomy, wedge resec tion of the underlying liver, and skeletonization of the hepatoduodenal ligament [19], However, the choice of operative procedures also depends on the depth of inva sion. At surgery, any suspicious lesion should be exam ined by frozen section.…”
Section: Discussionmentioning
confidence: 99%
“…In the University of Virginia series [16], of 100 reported pa-tients 92 were explored, and in 44 of these only biopsy with or without bypass was possible. From the remaining 48 who underwent resection, 40 had a cholecystectomy with or without common duct drainage, and 8 had cholecystectomy with partial liver resection.…”
Section: Surgical Managementmentioning
confidence: 99%